Janus and RG interfaces in three-dimensional gauged supergravity. Part II. General α - Michael Gutperle; Charlie Hultgreen-Mena (Journal of High Energy Physics, 2022)
Abstract In this paper, we continue the study of Janus and RG-flow interfaces in three dimensional supergravity continuing the work presented in [1]. We consider N $$ \mathcal{N} $$ = 8 gauged supergravity theories which have a N $$ \mathcal{N} $$ = (4, 4) AdS 3 vacuum with D 1(2, 1; α) × D 1(2, 1; α) symmetry for general α. We derive the BPS flow equations and find numerical solutions. Some holographic quantities such as the entanglement entropy are calculated.